Inflation Targeting Lite - Stone, Mark (IMF Working Papers; Working Paper ;, 2003)
Inflation targeting lite (ITL) countries float their exchange rate and announce an inflation target, but are not able to maintain the inflation target as the foremost policy objective. This paper identifies 19 emerging market countries as practitioners of ITL. They seem to focus mainly on bringing inflation into the single digits and maintaining financial stability. ITL can be viewed as a transitional regime aimed at buying time for the implementation of the structural reforms needed for a single credible nominal anchor. The important policy challenges for an ITL central bank include whether or not to precommit to a single anchor.